Dynamic DNA architectures: spontaneous DNA strand exchange and self-sorting driven by perylene bisimide interactions. Issue 92 (30th September 2015) - Weiser, Martin; Wagenknecht, Hans-Achim
Abstract : Three differently bay-substituted perylene bisimides together with the conventional unsubstituted chromophore were synthetically incorporated as homodimers in DNA double strands and undergo spontaneous strand exchange if mixed together. Abstract : Three differently bay-substituted perylene bisimides together with the conventional unsubstituted chromophore were synthetically incorporated as homodimers in DNA double strands. If preannealed DNA duplexes with two different perylene bisimide homodimers are mixed together they undergo spontaneous DNA strand exchange. The dynamic self-sorting forms DNA architectures preferentially with perylene bisimide heterodimers and can be controlled by the electronic density in the chromophores.